Status survey of uncrossmatched type O suspended RBCs in patients with emergency transfusion - PENG Zhuoyue; XU Shilan; YANG Xinxin; CHEN Chunxia; TAN Bin (Zhongguo shuxue zazhi)
[Objective] To investigate the implementation of emergency transfusion strategy of uncrossmatched type O suspended RBCs based on the single-center clinical practice, which is "emergency transfusion is initiated by the authorized doctor of the emergency department, and no more than 4 U of type O uncrossmatched suspended RBCs are issued within 15 minutes in the transfusion department"(referred as the Practice), so as to provide reference for blood management. [Methods] A retrospective analysis of the information of patients who received uncrossmatched type O suspended RBCs in West China Hospital of Sichuan University from August 2019 to April 2024 was conducted. The analysis included reasons for emergency blood transfusion, time of receiving transfusion application and blood distribution, total bilirubin, indirect bilirubin, lactate dehydrogenase before and after transfusion, blood group of patients, and disease outcome. [Results] From August 2019 to April 2024, 39 cases applied for emergency transfusion of type O suspended RBCs, and a total of 90 U uncrossmatched suspended RBCs were transfused. All patients were Rh(D) positive, including 14 cases of blood group A, 6 cases of blood group B, 16 cases of blood group O, 2 cases of blood group AB, one case of undetermined blood group, and 2 cases with positive antibody screening. The main cause of emergency transfusion of type O suspended RBCs was traffic accident, accounting for 46% (18/39), with a mortality rate at 51.28% (20/39). The cause of death was primary injury, and no adverse reactions were reported. There was no significant difference in total bilirubin (TBIL), indirect bilirubin (IBIL) and lactate dehydrogenase (LDH) before and after blood transfusion (P>0.05). The median duration from admission to receiving transfusion application was 30.20 minutes, and 5.30 minutes from receipt of the application to blood distribution. [Conclusion] The single-center based Practice is safe, but there is room for optimization before the link of blood transfusion application sent to the transfusion department when applying for emergency transfusion of type O suspended RBCs.